Effect of Artificial Intelligence Features on Users’ Adoption Intentions of Mobile Banking Applications: Evidence from Egyptian Private Banks. - Din, Nouran Nour El; Tantawi, Dr. Passent Ibrahim; Ragheb, Dr. Mohamed A. (The journal of contemporary issues in business and government, 2023)
The main aim of this research is to advance understanding of the artificial intelligence features and its effects on adoption intention in the Egyptian private banks and minor aim examining if functional and psychological levels of evaluation have a mediating effect on the relation between artificial intelligence features and the adoption intention. The objectives of this research are: to examine the relationship between artificial intelligence features and the adoption intention , to test the relationship between artificial intelligence features and functional level of evaluation , to investigate the relationship between artificial intelligence features and psychological level of evaluation , to examine the relationship between functional level of evaluation and the adoption intention, to investigate the relationship between psychological level of evaluation and adoption intention , to examine the mediation role of functional level of evaluation between artificial intelligence features and adoption intention. Finally, to investigate the mediation role of psychological level of evaluation between artificial intelligence features and adoption intention. Data in this study came from a survey questionnaire of 445 acceptable responses. The results were analysed employing by Structural Equation Modeling technique (SEM) using Analysis Moment of Structures (AMOS) software. The main conclusions drawn from this study are: the direct effect between artificial intelligent features and adoption intention is statistically significant, the direct effect between artificial intelligent features and functional level of evaluation is statistically significant, the direct effect between artificial intelligent features and psychological level of Evaluation is statistically significant, the direct effect between functional level of evaluation and adoption intention is statistically significant, the direct effect between psychological level of evaluation and adoption intention is statistically significant. Moreover, the results of the mediation effect indicate that there is partial mediation effect of both functional and psychological levels of evaluation in the relationship between artificial intelligent features and adoption intention.